Time-loss and recurrence rate of lateral ankle sprains in male professional football players depending on the severity grade: do we trivialise LAS? - Karen Hambly; Zacharias Flore; Kyra De Coninck; Götz Welsch (BMJ Open Sport & Exercise Medicine)
Objectives Lateral ankle sprains (LAS) are among the most common injuries in professional football (soccer). Despite this, the severity and possible long-term consequences of LAS remain trivialised. This multicentre observational study in German elite football provides insights into time-loss and recurrence rates after LAS. Time-loss and recurrence rates are outcome measures vital for the future evaluation of rehabilitation protocols.Methods 798 male football players representing 34 teams from 13 professional German football clubs participated in this study during the 2021–2022 season, followed by a 12-month follow-up period. Data collection and reporting were carried out in accordance with the UEFA recommendations for the standardised collection of data on football injuries. Time-loss, recurrence rate and standardised severity grades (I–III) after LAS were recorded for professionals, U23, U19 and U17, respectively.Results A total of 187 ankle injuries were reported, with 115 out of the total being analysed. The overall time-loss was 29.89 days, with significant differences between youth elite players and professionals (32.96 vs 15.53 days lost; p<0.001). Professional players demonstrated the shortest time-loss in all LAS injury grades. Time-loss decreased with advancing age (R2=0.03, F(1, 106)=3.16, p=0.078). Grade I LAS’s time-loss differs significantly from grades II and III (p<0.001). A recurrent LAS was recorded in 34 players. The overall LAS recurrence rate was 25.6%.Conclusion This study provides data on time-loss and recurrence, which serve as reference values for future evaluation of rehabilitation concepts after LAS in elite football players.